India's pursuit of energy security : domestic measures, foreign policy and geopolitics - Sharma, Ashok, 1974- (SAGE Publications, 2019)
This book depicts vividly how energy security has become the prime driver for India's foreign policy and enabled the reshaping of our international relations.